Initial experiences with Multiplate® for rapid assessment of antiplatelet agent activity in neurosurgical emergencies - Beynon, Christopher; Scherer, Moritz; Jakobs, Martin; Jung, Carla Sabine; Sakowitz, Oliver; Unterberg, Andreas (Clinical neurology and neurosurgery, 2013)
Objective - As the population ages, physicians encounter a growing number of patients who are treated with antiplatelet agents and present with severe conditions requiring urgent neurosurgical therapy. Standard laboratory investigations are insufficient to evaluate platelet activity and furthermore, it is difficult to evaluate effects of haemostatic measures on platelet function. In this article we report our initial experiences with the point-of-care device Multiplate® for assessment of platelet activity in neurosurgical emergencies on patients with a reported intake of antiplatelet medication. - Methods - Multiplate® assessment of antiplatelet activity was carried out in 21 non-consecutive patients with a reported intake of antiplatelet medication (aspirin: n=21, clopidogrel: n=3, ticragrelor: n=1) and urgent admission to our hospital because of conditions such as intracranial haemorrhage requiring urgent neurosurgical therapy. Analysis was repeated in order to evaluate the effectiveness of haemostatic drugs and platelet concentrate transfusion on platelet activity in six patients. - Results - No technical difficulties occurred and in all cases, results were obtained within 15min. On admission, patients’ arachidonic acid induced platelet activity was reduced by 44.4±33.5% (range: −79.7% to +44.3%) compared to the lower reference limit. Two patients had a normal platelet activity despite a reported intake of aspirin. Haemostatic measures significantly increased arachidonic acid induced platelet activity by 100±66% (p<0.005). - Conclusion - The Multiplate® device allowed rapid assessment of antiplatelet agent activity and evaluation of haemostatic measures on platelet activity. Further studies with larger patient numbers are needed, but this device may represent a valuable tool to improve treatment modalities in patients treated with antiplatelet medication and conditions requiring urgent neurosurgical therapy.